Assessing service quality of community-based ecotourism: a case study from Kampung Kuantan Firefly Park - Othman, Mohd Shahwahid; Mohd Noor, Mohd Iqbal; Amir Mustafa, Amira Mas Ayu; M. S., Farah (Forest Research Institute Malaysia, 2013)
Community-based ecotourism (CBE) could offer business opportunities to local communities living within or adjacent to unique ecological sites. CBE focuses on impact of tourism on the community and takes environmental, social and cultural sustainability into account. To assess the extent that CBE has been practised in Malaysia, Kampung Kuantan Firefly Park (FP), a habitat of the Lampyridae species beetle, was selected as study site to evaluate the services that the park offered and to assess the ability of the service provider, with the participation from local stakeholders, to fulfil tourist requests using the criteria of CBE as guidelines. Data were collected using convenience sampling of international and domestic tourists using questionnaire. All questions had been prior tested for reliability. The method of analysis involved the critical incident technique to identify and assess the satisfaction or dissatisfaction of tourists with regard to service encounters at the park. Five service failure constructs were identified and prioritised, namely, dissatisfaction with the quality of attractions and facilities at the park, tourist expectations before the visit, inadequate knowledge of employees, unacceptable behaviours of employees and other tourists, and inadequate responses to tourist needs. The form of recovery strategies undertaken by the service provider, its employees and participating community for major service quality failures were recorded and their effectiveness assessed.